Use of amplified Mycobacterium tuberculosis direct test in respiratory samples from HIV-infected patients in Brazil - Barreto,Leonardo Bruno Paz Ferreira (2014)
OBJECTIVE: To compare the accuracy of the amplified Mycobacterium tuberculosis direct (AMTD) test with reference methods for the laboratory diagnosis of tuberculosis in HIV-infected patients. METHODS: This was a study of diagnostic accuracy comparing AMTD test results with those obtained by culture on Löwenstein-Jensen (LJ) medium and by the BACTEC Mycobacteria Growth Indicator Tube 960 (BACTEC MGIT 960) system in respiratory samples analyzed at the Bioassay and Bacteriology Laboratory of the Oswaldo Cruz Foundation Evandro Chagas Clinical Research Institute in the city of Rio de Janeiro, Brazil. RESULTS: We analyzed respiratory samples collected from 118 patients, of whom 88 (74.4%) were male. The mean age was 36.6 ± 10.6 years. Using the AMTD test, the BACTEC MGIT 960 system, and LJ culture, we identified M. tuberculosis complex in 31.0%, 29.7%, and 27.1% of the samples, respectively. In comparison with LJ culture, the AMTD test had a sensitivity, specificity, positive predictive value, and negative predictive value of 87.5%, 89.4%, 75.7%, and 95.0%, respectively, for LJ culture, whereas, in comparison with the BACTEC MGIT 960 system, it showed values of 88.6%, 92.4%, 83.8%, and 94.8%, respectively. CONCLUSIONS: The AMTD test showed good sensitivity and specificity in the population studied, enabling the laboratory detection of M. tuberculosis complex in paucibacillary respiratory specimens.